Ensuring Green Environment through Sustainable Development Goals in Thailand: Mediating Role of Supply Chain Integration - Kittisak Jermsittiparsert; Prapart Pintobtang; Surangrut Jumnianpol (International Journal of Supply Chain Management, 2019)
Increased global warming and industrial pollution have forced manufacturing organizations in Thailand to focus on sustainable practices. Such practices can come from Sustainable Development Goals (SDGs) which can contribute towards green environment either directly or indirectly. Supply chain integration can also play its role to bring all stakeholders at same page for ensuring green environment production. This study has investigated the impact of internal, customer and supplier sustainable development goals on environmental performance of manufacturing firms in Thailand. Furthermore, intervening role of supply chain integration has also been analyzed in relationship between SDGs and environmental performance. Data has been collected through questionnaire from middle level management of almost 49 manufacturing firms of Thailand which was subsequently analyzed on SPSS and AMOS for screening and path analysis. Results have confirmed the hypothesis that SGDs have significant impact on environmental performance and also flagged significant mediating role of supply chain integration in respective relationship. This research is original due to having a unique variable like supply chain integration and a completely different context of Thailand’s manufacturing sector which was not explored previously. This study will have its contribution in theory, practice and policy along with future research indications.